Safety Issues of Long-Term Glucose Load in Patients on Peritoneal Dialysis—A 7-Year Cohort Study - Vin‐Cent Wu; Kuan‐Yu Hung; Tao‐Min Huang; Fu‐Chang Hu; Yu‐Sen Peng; Jenq‐Wen Huang; Shuei‐Liong Lin; Yung‐Ming Chen; Tzong‐Shinn Chu; Tun‐Jun Tsai; Kwan‐Dun Wu (2012)
Background Effects of long-term glucose load on peritoneal dialysis (PD) patient safety and outcomes have seldom been reported. This study demonstrates the influence of long-term glucose load on patient and technique survival. Methods We surveyed 173 incident PD patients. Long-term glucose load was evaluated by calculating the average dialysate glucose concentration since initiation of PD. Risk factors were assessed by fitting Cox's models with repeatedly measured time-dependent covariates. Results We noted that older age, higher glucose concentration, and lower residual renal function (RRF) were significantly associated with a worse patient survival. We found that female gender, absence of diabetes, lower glucose concentration, use of icodextrin, higher serum high density lipoprotein cholesterol, and higher RRF were significantly associated with a better technique survival. Conclusions Long-term glucose load predicted mortality and technique failure in chronic PD patients. These findings emphasize the importance of minimizing glucose load in PD patients.